Investigation on Preparation and Application in Concrete of Physically Modified Fly Ash - Chunye, Zou; Zhengtang, Rao; Xingqin, Wang; Wenshang, Zhu; Zhisheng, Sun; Zhaomo, Ma; Qin, Huang; Xianxu, Feng; Zhongmao, Yang (Journal of Advanced Concrete Technology, 2024)
Raw fly ash (RFA) was modified by a self-developed new dry energy-saving vertical grinding mill. This was beneficial to improve the particle morphology and distribution of RFA and enhanced its practical applicability in cement and concrete. The physical modification mechanism of RFA was elucidated by simulating the grinding process, and the physical properties and the application performance of modified fly ash (MFA) were characterized. The results demonstrated that the new grinder can effectively realize the physical modification of RFA and significantly improve its properties because the porous structure and the intactness of glass beads of RFA are preserved without being destroyed. The fineness of MFA was improved to the standard of Class I or II fly ash, the 28 d strength activity index of which was increased by 7% to 17%. The fluidity of mortar was also improved by 15 to 34 mm. In addition, the water requirement ratio can be significantly reduced when MFA is used to prepare C30 and C45 concrete. The 28 d strength of concrete with 50% content of MFA was increased by 23.76% and 15.84%, respectively. These results suggest that the grinding process studied here is a novel method for improving the performance of MFA.